Finden Sie die Lösung von h (x) = k (x) mit h (x) = -4x + 16 und k (x) = 10x + 44?

Antworten:

# x = -2 #

Erläuterung:

# "gegeben" h (x) = k (x) "dann" #

# -4x + 16 = 10x + 44 #

# "10x von beiden Seiten abziehen" #

# -4x-10x + 16 = Abbrechen (10x) Abbrechen (-10x) + 44 #

# rArr-14x + 16 = 44 #

# "16 von beiden Seiten abziehen" #

# -14xcancel (+16) stornieren (-16) = 44-16 #

# rArr-14x = 28 #

# "beide Seiten teilen durch" -14 #

# (Abbruch (-14) x) / Abbruch (-14) = 28 / (- 14) #

# rArrx = -2 "ist die Lösung" #